THE AFFECT OF VIGOR, DEDICATION AND ABSORPTION ON THE EMPLOYEE PERFORMANCE AT PT. MANDIRI UTAMA FINANCE - Srie Intan Maisyuri, Ratih; Ariyanto, Eny (Dinasti Publisher, 2021)
This research has purpose to revealed those affect from all dimensions of employee engagement, which is vigor, dedication and absorption on the performance of employees at PT. Mandiri Utama Finance. The aims of this research was to discovered an descriptive explanation relates to the vigor, dedication, absorption and also employees performance at PT. Mandiri Utama Finance and it affects towards the performance of employees at PT. Mandiri Utama Finance. The research population was all employees of PT. Mandiri Utama Finance, which amounted of 210 people. Due to the relatively small population, so all the employees were made as respondents (saturated sampling). The data analysis method used multiple linear regression analysis by SPSS (Statistical Package for The Social Sciences) software version 25. The results showed that vigor had a positive and significant affect on employee performance, dedication had a positive and significant affect on employee performance and absorption had a positive and significant affect on employee performance. All above variables has a weak impact with coefficient of determination (R²) only for 32%.